Transcriptomic insights into antagonistic effects of gibberellin and abscisic acid on petal growth in Gerbera hybrida - Li, Lingfei; Zhang, Wenbin; Zhang, Lili; Li, Na; Peng, Jianzong; Wang, Yaqin; Zhong, Chunmei; Yang, Yuping; Sun, Shulan; Liang, Shan; Wang, Xiaojing (Frontiers in Plant Science, 2015)
Petal growth is central to floral morphogenesis, but the underlying genetic basis of petal growth regulation is yet to be elucidated. In this study, we found that the basal region of the ray floret petals of Gerbera hybrida was the most sensitive to treatment with the phytohormones gibberellin (GA) and abscisic acid (ABA), which regulate cell expansion during petal growth in an antagonistic manner. To screen for differentially expressed genes (DEGs) and key regulators with potentially important roles in petal growth regulation by GA or/and ABA, the RNA-seq technique was employed. Differences in global transcription in petals were observed in response to GA and ABA and target genes antagonistically regulated by the two hormones were identified. Moreover, we also identified the pathways associated with the regulation of petal growth after application of either GA or ABA. Genes relating to the antagonistic GA and ABA regulation of petal growth showed distinct patterns, with genes encoding transcription factors (TFs) being active during the early stage (2 h) of treatment, while genes from the “apoptosis” and “cell wall organization” categories were expressed at later stages (12 h). In summary, we present the first study of global expression patterns of hormone-regulated transcripts in G. hybrida petals; this dataset will be instrumental in revealing the genetic networks that govern petal morphogenesis and provides a new theoretical basis and novel gene resources for ornamental plant breeding.